Analysis of the Influence of Human Capital on Poverty in North Sumatra 2020 – 2022 - Diki Purnomo; Harahap, Kartiyani; Nadeak, Royan Abel; Sitepu, Yoga Erguna; Hidayat, Nasrullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the impact of human capital variables on poverty levels in the North Sumatra region. Human capital is measured through education, health and employment factors. The multiple regression method is used to understand the extent to which human capital variables influence poverty levels in this region. This research uses quantitative methods with a multiple regression analysis model. As a result of data analysis, several important conclusions can be drawn regarding the influence of human capital on poverty levels in North Sumatra. This research examines and analyzes the impact of human capital (education, health and employment) on poverty levels in North Sumatra Province. The research conclusion shows that there is a significant and positive influence simultaneously between education, health and employment on poverty levels. Apart from that, partially, education, health and employment also have a significant and positive influence on reducing poverty levels. With an increase in these three variables, the poverty level tends to decrease significantly and positively.